Effect of Combined Wave and Current Loading on the Hydrodynamic Characteristics of Double-Pile Structures in Offshore Wind Turbine Foundations - Yongqing Lai; Li Cai; Xinyun Wu; Bin Wang; Yiyang Hu; Yuwei Liang; Haisheng Zhao; Wei Shi (Energies)
The multi-pile structure is a common and reliable foundation form used in offshore wind turbines (such as jacket-type structures, etc.), which can withstand hydrodynamic loads dominated by waves and water flow, providing a stable operating environment. However, the hydrodynamic responses between adjacent monopiles affected by combined wave and current loadings are seldom revealed. In this study, a generation module for wave–current combined loading is developed in waves2Foam by considering the wave theory coupled current effect. Subsequently, a numerical flume model of the double-pile structure is established in OpenFOAM based on computational fluid dynamics (CFD) and SST k-ω turbulence theory, and the hydrodynamic characteristics of the double-pile structure are investigated. It can be found that, under the combined wave–current loading, the maximum wave run-up at the leeward side of the upstream monopile is significantly reduced by about 24% on average compared with that of the individual monopile when the spacing is 1.25 and 1.75 times the wave length. At the free water surface height, the maximum discrepancy between the maximum surface pressure on the downstream monopile and the corresponding result of the individual monopile is significantly reduced from 37% to 19%. Compared to the case applying the wave loading condition, the wave–current loading reduces the influence of spacing on the wave run-up along the downstream monopile surface, the maximum surface pressure at specific positions on both upstream and downstream monopile, and the overall maximum horizontal force acting on the double-pile structure.